Autosomal recessive genetic disorders of cattle breeds Worldwide- a Review - R. K. Patel (Journal of Livestock Biodiversity, 2025)
The present review briefly describes autosomal recessive disorders observed among various breeds of cattle worldwide.  These disorders in cattle may occur at very low to low frequency and therefore, carriers are usually not detected in breeding programmes. The autosomal recessive genetic diseases are mostly breed-specific which can be detected by simple techniques like Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and other molecular tools.